Anesthetic considerations for combined heart–liver transplantation in patients with Fontan-associated liver disease. Issue 5 (October 2020) - Hofer, Ryan E.; Christensen, Jon M.; Findlay, James Y.
Abstract : Purpose of review: The success of the Fontan procedure has led to increased survival of patients born with certain congenital heart disease to the point that new sequlae, as a result of Fontan circulation, are being discovered. Included among these is Fontan-associated liver disease (FALD). The purpose of this review is to present available literature on the perioperative management of the combined heart–liver transplantation (CHLT) in patients with FALD. Recent findings: The perioperative management of a combined heart-liver transplant in a patient with Fontan circulation is complex. The patient is at risk for hemodynamic disturbances, significant blood loss, coagulopathies, and metabolic derangements. The maintenance of an appropriate transpulmonary pressure gradient is paramount to success. Postoperative management should be accomplished by a multidisciplinary care team. Limited series have demonstrated good outcomes in patients who have undergone CHLT. Summary: The perioperative management of CHLT in patients with FALD is complex and available literature is limited. Future studies are needed to further assess proper perioperative management of patients with FALD who undergo CHLT.